Endangering the principle of secularity with new legal solutions in the Republic of Serbia - Lazović, Miljan; Ilić, Dušan (Sociološki pregled, 2021)
In this paper, the authors deal with the analysis of new antidiscrimination legal solutions proposed by the Ministry of Human and Minority Rights and Social Dialogue of the Government of the Republic of Serbia, which would redefine the relations between the state and the church. The focus of the research will be especially on those solutions that could threaten, on the one hand, the principle of secularity, and on the other hand, some of the fundamental human rights, such as the right to freedom of thought, conscience and religion. The solutions proposed by the amendments to the Law on Prohibition of Discrimination, it seems, could be problematic from the standpoint of guaranteeing certain fundamental human rights and freedoms, but also the autonomy of churches and religious communities. Some of the proposals made by the Ministry could be seen as an attempt to return the verbal offence to the Serbian legal system. Accordingly, the authors will try to re-examine the possible impact of changes in antidiscrimination legislation on the relationship between the state and the church, but also on the possible suppression of religious rights and freedoms in the Republic of Serbia in the coming period.
Keywords: secularity; churches and religious communities; freedom of religion; discrimination